Effect of In-Office Carbamide Peroxide-Based Tooth Bleaching System on Wear Resistance of Silorane-Based and Methacrylate-Based Dental Composites - Masoumeh Hasani Tabatabaei; Sedigheh Sheikhzadeh; Hamidreza Ghasemi Monfared Rad; Ahmad Beygi; Hossein Bagheri (Tehran University of Medical Sciences, 2016)
Objectives: Several studies have assessed the characteristics and properties of silorane-based composites and adhesive systems. Considering the extensive application of tooth-whitening agents, possible deteriorative effects of tooth bleaching agents on these restorative materials must be studied. The aim of this study was to evaluate the effect of an in-office carbamide peroxide-based tooth bleaching agent on the wear resistance of a silorane-based and a conventional microhybrid dimethyl methacrylate-based dental composite with two different application times.   Materials and Methods: Thirty cylindrical specimens were made of Z250 and P90 dental composite resins (n=15 for each composite). Samples made of each composite were divided into three groups (n=5) for immersion in an in-office bleaching agent (Opalescence® Quick 45%) for either three or eight hours or saline solution (control). Wear tests were conducted after bleaching using a pin-on disk apparatus under the load of 40N at a constant sliding speed of 0.5 ms-1 for a sliding distance of 300 m. The samples were weighed before and after the wear test. Repeated measures ANOVA was used to statistically analyze the obtained data (α=0.05). Results: There was a significant decrease in the weight of samples after the wear test (P<0.001). However, no significant difference was found among groups in the mean weight of samples before and after the wear test (P>0.05).  Conclusion: Bleaching for three or eight hours using 45% carbamide peroxide had no deteriorative effect on the wear resistance of Z250 and P90 composites.